Correlation between 99mTc-TRODAT-1 SPECT and 18F-FDOPA PET in patients with Parkinson’s disease: a pilot study - Arena,Julieta E. (2021)
Abstract Objective: To determine whether technetium-99m-labeled tropane derivative single-photon emission computed tomography (99mTc-TRODAT-1 SPECT) provides results comparable to those of the less widely available, less accessible tool fluorine-18-labeled fluorodopa positron-emission tomography (18F-FDOPA PET) in the setting of a movement disorders clinic. Materials and Methods: In this prospective pilot study, eight subjects with a clinical diagnosis of Parkinson’s disease were randomly selected from among patients under treatment at a movement disorders clinic and submitted to 99mTc-TRODAT-1 SPECT and 18F-FDOPA PET. The results were read by two experienced observers, and a semiquantitative analysis was performed. Results: The visual and semiquantitative analyses were concordant for all studies, showing that radiotracer uptake in the contralateral striatum on the most affected side was lower when 99mTc-TRODAT-1 SPECT was employed. The semiquantitative analysis demonstrated a significant correlation between 18F-FDOPA PET and 99mTc-TRODAT-1 SPECT (r = 0.73; p < 0.01). Conclusion: It appears that 99mTc-TRODAT-1 SPECT is a valid option for the study of dopaminergic function in a clinical setting.